19 Time From Symptoms Onset to Diagnosis and Optimum Therapy; Does It Relate to Outcome in Heart Failure Patients?. (3rd June 2016) - Wahab, Ali; Jamil, Haqeel; Gierula, John; Paton, Maria; Byrom-Goulthorp, Roo; Sunley, Emma; Winsor, Sarah; Cubbon, Richard; Kearney, Mark; Witte, Klaus
Abstract : Introduction: Current National Institute of Health and Care Excellence (NICE) guideline recommendations on diagnosing heart failure (HF) in primary care include the measurement of serum natriuretic peptide concentrations (NP). NP concentrations are raised in HF related to severity. In addition to advising a referral above an 'intermediate' level (to be seen within 6 weeks), the guidelines suggest that patients with 'high' levels should be seen more urgently (within 2 weeks). This prospective service evaluation aimed to provide evidence to support this challenging requirement by exploring the impact of time from symptoms onset to diagnosis and optimum treatment on subsequent long-term mortality in patients with HF due to left ventricular systolic dysfunction (LVSD). Methods: We recorded date of symptom onset, referral, diagnosis and subsequent mortality in 206 patients newly diagnosed with HF due to LVSD seen in clinic following a NP test over twelve months from May 2012. The primary investigator (AW) was blinded to the NP result. Patients were initially divided into groups 'high' and 'intermediate' and then by whether they were seen within NICE-stipulated timeframes (n = 71) or not (n = 109). Due to a limited number of events, outcomes have been pooled using the 6 weeks cut-off. All-cause mortality was plotted on Kaplan-Meier curves and logistic regression was used to determine whether times between points on the pathway and being seen within 6 weeks featured in models including other known predictors of mortality. Results: After a mean follow-up time of 411 days (range (219–255 days)) 24 patients with a raised NP result had died (15%). Mean clinic visit time from the date of the blood test was 60 days (range (57–63 days)). Kaplan-Meier curves indicated no difference in mortality for patients seen within 6 weeks according to NP levels and those seen later than 6 weeks (p = 0.49). Conclusion: In patients presenting to their primary care physician with symptoms possibly due to heart failure, subsequently confirmed to have LVSD, there is no difference in outcomes if they are seen within 6 weeks or not. The guideline that patients with symptoms possibly due to HF and a raised NP level should be seen within 6 weeks, has the potential to lead to great pressure on all outpatient cardiology services yet seems to have no impact on mortality. Whether hospitalisation is avoided by urgent referral remains to be assessed.